(untitled) (Sustainability in Debate, 2018)
The advent of new technologies in last mile deliveries is about to cause a disruption in the traditional business model applied in urban cargo transportation. Along these lines, transport operators try to obtain economic returns, not only by optimizing traditional strategies, but also by seeking to establish strategies based on the bottom-line of sustainability. This paper aims to identify studies that proposes alternative vehicles that could be used in the last mile of urban freight transport to reduce the energy efficiency while improve its efficiency. To state the literature gap, we conduct a systematic literature review on energy efficiency in urban freight transportation, converting the last mile deliveries into a sustainable operation. Results indicate a trend towards the implementation of smaller and lighter vehicles for last mile deliveries in urban areas: 95% of studies suggest, among other alternatives, the use of bicycles and tricycles; while 53% of articles support the use of light commercial vehicles. Another trend observed in this type of distribution, indicated in 77.3% of the studies, is the shift from conventional fuels (fossil fuels) to alternative sources of energy (electricity).